Preliminary survey of farmers compliance on proper herd health program practice among goat farms under Ladang Angkat Program, Faculty of Veterinary Medicine, UPM - Rofie, Abdul Muhaimin (2015)
Good herd health management will help to prevent the development and spread of diseases and reduces economic losses. However, there is lack of information regarding the farmers’ compliance on proper herd health program (HHP) practised by the small ruminant farms in Malaysia. Therefore, a survey was conducted to study the farmers’ compliance on HHP practised at selected goat farms (n=6) in Ladang Angkat Program, Faculty of Veterinary Medicine, UPM. Structured questionnaires was developed based on the Skim Amalan Ladang Ternakan (SALT) by Department of Veterinary Services (DVS) of Malaysia. The scores were given in percentage according to the farmers’ knowledge and practice on every component of HHP. All of the farms surveyed were managed in intensive system mainly for meat production. Most farmers (83.3%) were aware of the existence of herd health program. Farmers (n=6) scored 56±7% (mean) for overall HHP practice with maximum score on waste management (75%) followed by environmental management (73%), parasite control program (70%), biosecurity (67%), feeding management (59%), drug management (59%), disease monitoring program (54%) and minimum score on reproductive management (48%). No farmers practiced the vaccination program in their farm. However, all farmers were willing to invest money for herd health program that guarantee long term profitability in the future. In conclusion, more attention and exposure need to be given on the HHP components that are less complied by the farmers without neglecting the other components for future development of improvised herd health programs.